Analisis Hukum Aborsi menurut Fatwa MUI dan PP Nomor 61 Tahun 2014 tentang Kesehatan Reproduksi - Risma Octaviani (Bandung Conference Series: Islamic Family Law, 2023)
Abstract. Pregnancy is something that most married couples look forward to, but not a few couples choose to delay their pregnancy for one reason or another, one way to delay pregnancy is to use contraception. However, in their use, not all cityception tools functioned as they should, as happened in Kampung Patrol, Ciamis Regency, there were cases of pregnancies that had to be aborted due to medical emergencies for the mother and the fetus in the womb. The MUI Fatwa and Government Regulation Number 61 of 2014 formulate reproductive health and permissibility in the practice of abortion. Researchers in their research formulated the following problem formulation: What are the legal provisions for abortion according to the MUI fatwa and Government Regulation No. 61 of 2014 concerning reproductive health; What is the practice of abortion in Patrol Village, Sukamantri District; What is the legal analysis of abortion due to the use of contraceptives according to the MUI fatwa and PP No. 61 of 2014; As for the purpose of this study is to answer the formulation of the problem. This research is a field research, using a qualitative descriptive analysis technique. The results of the researcher's research that in principle abortion is prohibited, but with the terms and conditions that abortion is allowed, namely as a result of medical indications and pregnancy due to rape. The practice of abortion carried out in Patrol Village as a result of the use of contraceptives which results in medical emergencies and genetic defects in the fetus. The practice of abortion resulting from the use of contraceptives that are not in accordance with the procedure, according to government regulations and the MUI fatwa, abortion due to medical indications is permissible. Abstrak. Kehamilan adalah satu hal yang sangat dinanti-nantikan oleh kebanyakan pasangan suami istri, namun tidak sedikit juga pasangan suami istri yang memilih menunda kehamilannya karena satu dan lain hal, salah satu cara menunda kehamilan yaitu dengan menggunakan alat kontrasepsi. Namun, dalam penggunaanya tidak semua alat kotasepsi berfungsi sebagaimana mestinya, seperti halnya yang terjadi di Kampung Patrol Kabupaten Ciamis terdapat kasus kehamilan yang harus dilakukan tindakan aborsi akibat terjadi kedaruratan medis pada ibu dan janin yang di kandung. Fatwa MUI dan Peraturan Pemerintah Nomor 61 Tahun 2014 merumuskan tentang Kesehatan reproduksi dan kebolehan dalam praktek aborsi. Peneliti dalam penelitiannya merumuskan rumusan masalah sebagai berikut: Bagaimana ketentuan hukum aborsi menurut fatwa MUI dan Peraturan Pemerintah No 61 tahun 2014 tentang Kesehatan reproduksi; Bagaimana praktek abosi di Kampung Patrol Kecamatan Sukamantri; Bagaimana analisis hukum aborsi akibat penggunaan alat kontrasepsi menurut fatwa MUI dan PP No 61 Taun 2014; adapun tujuan dari penelitian ini yaitu menjawab rumusan masalah. Penelitian ini merupakan penelitian lapangan (field research), menggunakan teknik analisis deskriptif kualitatif. Hasil penelitian ditemukan secara prinsip aborsi dilarang namun karena indikasi medis dan akibat kehamilan akibat pemerkosaan diperbolehkan ; praktek aborsi yang terjadi di kampung patrol yang di akibatkan dari kesalahan penggunaan kontrasepsi yang mengakibatkan adanya cacat genetik dan kedaruratan medis; praktek seperti demikian menurut fatwa mui dan pp nomor 61 tahun 2004 membolehan melakukan tindakan aborsi.